The Tata Kelola Pertambangan Berbasis Aplikasi SIMBARA Sebagai Pencegahan Kerugian Keuangan Negara - Kurniatul, Anisa; Bagus Teguh Santoso (INTELEKTUAL ( E-Journal Administrasi Publik dan Ilmu Komunikasi ), 2025)
This study aims to assess the effectiveness of the implementation of the Mineral and Coal Information System (SIMBARA) in supporting the digital transformation of mining sector governance in Indonesia and its role in preventing potential state financial losses. SIMBARA has been developed as an integrated platform connecting various ministries and government agencies to ensure transparency, accountability, and efficiency in the end-to-end management of mineral and coal resources. The research adopts a qualitative descriptive approach through literature review, with data analysis based on the “Miles and Huberman model”, encompassing data reduction, data presentation, and conclusion drawing. Data sources include regulations, government evaluation reports, scientific journals, and relevant academic documents published since 2015. The findings reveal that SIMBARA has successfully integrated cross-sectoral systems such as MODI, MOMS, e-PNBP, and SIMPONI, contributing to enhanced regulatory oversight, expedited licensing processes, and optimized state revenue from Non-Tax State Revenue (PNBP) and taxation. Furthermore, SIMBARA has proven effective in identifying illegal mining activities and various fraudulent schemes, including manipulation of the State Revenue Transaction Number (NTPN). The implementation of this system has been recorded to prevent potential state financial losses amounting to IDR 7.71 trillion during the 2022–2024 period. These findings affirm that SIMBARA serves as a critical foundation for the digitalization of national mining governance that is adaptive, integrated, and sustainable.